Anaplastic Ependymoma With Ganglionic Differentiation: Report of a Rare Case and Implications in Diagnosis. (October 2017) - Rao, Shilpa; Ravindra, Niveditha; Sadashiva, Nishanth; Indira Devi, Bhagavatula; Santosh, Vani
Ependymomas are glial neoplasms with rare cases exhibiting neuronal differentiation. We describe a case of spinal anaplastic ependymoma with ganglionic differentiation in a 28-year-old woman. The ganglionic component was labeled by synaptophysin, whereas the rest of the tumor showed features of an anaplastic ependymoma. Stem cell marker MELK was noted to stain both the neoplastic ependymal and ganglionic components, possibly suggesting a stem cell/progenitor origin for the tumor with subsequent divergent differentiation.